Príprava a využitie kombinovaných adsorbentov na zeolitovej báze pri odstraňovaní oxyaniónových polutantov z vôd - Sabová, Lenka; Chmielewská, Eva; Gáplovská, Katarína (Chemické listy, 2010)
Natural zeolites are very popular in environment remediation due to their abundance and cost effectiveness. Their large surface area offers surface modification to improve their adsorption properties. The aim of the study is to develop combined adsorbents based on zeolites and alginates for removal of oxyanions from water. The combined adsorbents were prepared by mixing powdered zeolite and alginate, which, in the presence of divalent cations like Ca2+ form hydrogel beads. The Ca(II)-alginate-zeolite beads were further treated with Fe3+ cations to enhance their adsorption capacity. The zeolite/alginate ratio in the adsorbent was studied in order to find the most effective adsorbent. Kinetics of nitrate and sulfate adsorption were investigated. From the measured data, adsorption isotherms were obtained and evaluated.
Keywords: Nitrates; Water Pollutants; zeolity; sírany; Sulfates; regenerace a remediace životního prostředí; Zeolites; adsorpce; Environmental Restoration and Remediation; Adsorption; dusičnany; látky znečišťující vodu